Considering religious education in context politics, reform and debates among Turkish Cypriots - Latif, Dilek (2019)
This article exemplifies the politicisation of religious education that has polarised the Turkish Cypriot community and explores a possible approach to religious education for primary schools in north Cyprus. In the light of the long-standing debate, this study has a particular focus on the mandatory religious instruction in public primary schools and evaluates the textbooks and teachers' perceptions. Unlike lower and upper secondary schools, divinity classes have constantly been offered to primary school pupils since the 1960s. Religious education at the primary school level is a contentious issue on which the educational experts have been unable to reach a consensus, and continue to discuss on different perspectives. To this end, a comprehensive review of the content analysis of the primary school religious education textbooks and semistructured interviews with teachers and education specialists has been undertaken. Although this study is set in the north Cyprus context, it is also relevant for other conflict-affected societies as it describes the challenges of religious education, secularism and pluralism.
Keywords: Politicisation of religious education; north Cyprus; Primary School; public debates